Analysis of color changes in chicken egg yolks and whites based on degree of thermal protein denaturation during ohmic heating and water bath treatment. (April 2018) - Llave, Yvan; Fukuda, Satoshi; Fukuoka, Mika; Shibata-Ishiwatari, Naomi; Sakai, Noboru
Abstract: Raw eggs were separated into yolks and whites before thermal treatment. An ohmic heating process at 20 kHz and 30 V was used for egg-yolk samples, and color changes were monitored with a computer vision system. Egg-white samples were treated with a water bath, and absorbance, as an expression of turbidity, was determined spectrophotometrically. Thermal protein denaturation of egg samples was analyzed by differential scanning calorimetry (DSC) using the dynamic method, and estimated for several thermal schedules by kinetics analysis. The DSC thermogram was characterized by two endothermic peaks in each sample. With increasing temperature, the yolk gradually turned from a plain orange to a vivid yellow color, while the white gradually changed from transparent to cloudy. For all samples, an accurate correlation was obtained between color changes and the non-denaturation ratio of the second peak temperature. Results are of potential value for the modeling and design of egg-based products. Highlights: Kinetics parameters of the reduction rate of protein denaturation of egg yolks and whites were obtained. Changes in color of egg yolks during OH were evaluated using computer vision system. Changes in turbidity of egg white during water bath treatment were evaluated by spectrophotometer. Egg color changes were correlated with the non-denaturation ratio of the second peak temperature.